Effect of home-based pulmonary rehabilitation using a woven rubber chain on the quality of life of COPD patients in Chiang Dao district, Chiang Mai, Thailand - Intravong, Kotchaporn (Biomedical Sciences and Clinical Medicine, 2019)
Objective To determine the effectiveness of using a woven chain of rubber bands as an exercise device in home-based pulmonary rehabilitation (HBPR) in improving exercise capacity (6MWD), health-related quality of life (HRQoL) and prognosis (BODE index) in COPD patients. Methods An 8-week randomized controlled trial (RCT) single blind (assessor blind) study was conducted with 30 COPD patients, 15 in the intervention group and 15 in the control group. All patients participating in the HBPR program were pre and post evaluated for lung function via spirometry, exercise capacity via 6MWD, HRQoL via SGRQ, and prognosis via BODE index. All scores were compared using the Paired t-Test within groups and the Independent t-Test between groups. Statistical significance was set at p<0.05. Results Exercise using a woven chain of rubber bands for HBPR therapy improved exercise capacity (6MWD) by 26.67±39.20 meters (p<0.01), SGRQ score (impact domain) by -19.41±14.13 points (p<0.04) and BODE index score by -0.06±16.68 points (p<0.03) compared to the control group in which both 6MWD and BODE index declined. Conclusion HBPR using a woven chain of rubber bands is effective in improving exercise capacity (6MWD), health related quality of life (SGRQ), and disease prognosis (BODE index) in COPD patients. The model regime used in this study is practical and is likely to be complied with. HBPR using a woven chain of rubber bands is easy to access and helps eliminate the need to travel to an exercise facility. Long-term results and potential problems still need to be closely monitored.